The Reasons of Boycotting Consumers and Supply Chain (case study: India) - Rajnish Shankhdhar; Nimish Gupta (International Journal of Supply Chain Management, 2018)
Abstract- The article attempts to ascertain the positive and negative reasoning associated with boycotting a consumer and supply chain. Many have been mentioned in various write ups as to how a consumer boycott is organized and what are the features involved in it, but there are numerous reasons in todays marketplace that can either cause a consumer boycott and supply chain boycott to achieve what it intends to or simply fail for not carrying enough background. To successfully accomplish its motive, it becomes imperative to study what makes a boycott successful and what can cause it to be unsuccessful. Though, consumers are important to organize their protest, but not all protests can be instrumental towards a successful boycott, if it is the nature of detriment and the role of media that can either make a boycott, the same can be responsible to break a boycott midway. The article Attempts to ascertain the reasoning of success and failure in boycotting the consumer and supply chain. The study becomes important because many boycotts have been successful, but many went unnoticed in recent years, a sample size of 100 respondents has been surveyed with findings on primary data being discussed systematically. Key words: Boycott, Ethical, detriment, Consumers, Supply Chain, India.